Tasting Islam - Abenante, Paola (Enthalten in:Culture and religion;Abingdon : Taylor & Francis, 2000;18(2017), 2, Seite 129-148, 2017)
This article describes the convergence of Sufi and modern traditions of thought within ritual practices in an Egyptian brotherhood and its Europeans branches. I disentangle the different threads behind one of my interlocutor’s words and experience of dhawq (taste), a spiritual sense that in Sufi tradition reconnects the disciple to the divine. I argue that the way my interlocutors experience dhawq builds up into a form of religious aesthetics and architecture of the self that draw on the encounter with European psychological traditions. Distinctive in this encounter is that the self emerges as the location of an experience that is always, and already, an experience of transcendence, of an outside that is constitutive of selfhood. By putting into dialogue two traditions of knowledge that stand at the margins of the modern world, namely the esoteric trend of Sufi tradition and the Gestalt tradition, my interlocutors’ religious aesthetics promotes an architecture of the self that is alternative to hegemonic understandings of modern Islam structuring the contemporary Egyptian public sphere, as it foregrounds divine intervention and backgrounds individual responsibility and action.
Keywords: modernity; psychology; subjectivity; Sufism; transcendence